Effective health management strategies for patients undergoing valve replacement: a bibliometric analysis of the current research status and future directions - Wang, Xiaohui; Wu, Ying; Li, Ming; Wen, Jing; Liu, Lijuan; Huang, Wenzhuo; He, Qianqian; Liao, Yongzhen; Cong, Li (Frontiers in Cardiovascular Medicine, 2024)
Background Valvular heart disease is a major health concern worldwide. The effective management of patients undergoing valve replacement determines their prognosis. Bibliometric analysis of studies on managing patients with artificial heart valves has not been previously performed. Methods This study analyzed 2,771 publications related to patient management after valve replacement published in the Web of Science Core Collection database between January 1, 2013, and December 31, 2022. Bibliometric analysis was performed using CiteSpace and VOSviewer considering countries, institutions, authors, journals, references, and keywords. Results The countries with the most significant contributions in this field were the United States of America (USA), Germany, and Italy. Leon MB from Columbia University, USA was the most influential author. Transcatheter aortic valve replacement was a current research hotspot, while anticoagulation management was a key area of interest. Combining anticoagulation therapy with internet-linked tools and portable health devices may offer new research avenues. Frailty assessment and intervention were potential future research areas. Conclusions This bibliometric analysis provides clinicians and researchers with useful insights for developing novel ideas and directions to manage the health of patients undergoing valve replacement.